2019
DOI: 10.3390/ijms21010258
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Non-Coding RNAs in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a highly prevalent tumor and is associated with ethnicity, genetics, and dietary intake. Non-coding RNAs (ncRNAs), specifically microRNAs (miRNAs), long ncRNAs (lncRNAs), and circular RNAs (circRNAs) have been reported as functional regulatory molecules involved in the development of many human cancers, including ESCC. Recently, several ncRNAs have been detected as oncogenes or tumor suppressors in ESCC progression. These ncRNAs influence the expression of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 152 publications
(150 reference statements)
1
57
0
Order By: Relevance
“…miRNAs play important regulatory roles in cell differentiation, proliferation, invasion, metastasis, and apoptosis (9). Currently, data are available on the miRNA signature of ESCC, and there are studies attempting to point out the potential value of miRNAs in ESCC screening, diagnosis, treatment, and prognosis (10). miR-216a-5p is a member of the miR-216 family (miR-216a/miR-216b), which has been shown to be dysregulated in several types of human cancers (11)(12)(13)(14)(15)(16).…”
Section: Microrna-216a-5p Suppresses Esophageal Squamous Cell Carcinomentioning
confidence: 99%
“…miRNAs play important regulatory roles in cell differentiation, proliferation, invasion, metastasis, and apoptosis (9). Currently, data are available on the miRNA signature of ESCC, and there are studies attempting to point out the potential value of miRNAs in ESCC screening, diagnosis, treatment, and prognosis (10). miR-216a-5p is a member of the miR-216 family (miR-216a/miR-216b), which has been shown to be dysregulated in several types of human cancers (11)(12)(13)(14)(15)(16).…”
Section: Microrna-216a-5p Suppresses Esophageal Squamous Cell Carcinomentioning
confidence: 99%
“…Recent studies on lncRNAs have attracted increasing attention due to the involvement of these molecules in cancer oncogenesis and progression ( 38 - 40 ). Studies have reported the expression of hundreds of lncRNAs in ESCC, and differentially expressed lncRNAs have been shown to be closely related to ESCC malignancy through their effects on a wide range of tumor behaviors ( 41 , 42 ). Therefore, it is necessary to clarify the functions of lncRNAs in ESCC and thus identify effective diagnostic markers and treatment targets.…”
Section: Discussionmentioning
confidence: 99%
“…The role of lncRNAs in ESCC formation and progression has gradually emerged [5]. LncRNA FAM83H-AS1 has been reported to play an oncogenic role in tumors by modulating cell proliferation, migration and invasion [11,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing ndings support that long noncoding RNAs (lncRNAs) are crucial regulators in ESCC formation and progression [5][6][7][8][9][10]. Some lncRNAs modulate ESCC cell migration and invasion, and might be novel prognostic indicators, speci cally, biomarkers, for the early detection of metastasis in ESCC [5,9]. For instance, lncRNA DLX6 antisense RNA 1 (DLX6-AS1) expression was signi cantly increased in ESCC tissues, and DLX6-AS1 knockdown inhibited ESCC cell proliferation, migration and invasion [6].…”
Section: Introductionmentioning
confidence: 99%